A laminar kinetic energy transition model appropriate for hypersonic flow heat transfer. (April 2017) - Qin, Y.P.; Yan, C.; Hao, Z.H.; Zhou, L.
Highlights: The kT -kL -ω transition model is revised for hypersonic flows. Unstable modes in hypersonic flows are taken into consideration. The increase of heat flux caused by transition is well captured. The revised transition model reflects the effect of Reynolds number successfully. Abstract: A laminar kinetic energy transition model appropriate for hypersonic flow heat transfer is proposed in this paper. Based on the laminar kinetic energy transition model at low speed, three rectifications are made to make it possess the ability to predict hypersonic flow transition. Firstly, turbulence length scale is revised to consider boundary layer information directly and reflect the kinematic wall effect correctly at hypersonic speed. Secondly, large-scale eddy viscosity is reconstructed to take hypersonic unstable modes into account to describe the procedure of flow instability. Additionally, for the sake of a better results of the full-turbulence simulation and to be compatible with the revised transition model, the eddy viscosity in sheer stress transport model is adopted to substitute for small-scale eddy viscosity. The model has been applied to a number of relevant test cases, including flat plate boundary layers and boundary layer transition over a blunt cone at different Reynolds numbers. The test cases demonstrate the capacity of the model to reproduce transition flow behavior with a reasonable degree of accuracy and reflect the effect of Reynolds number successfully. While it still needs further investigation to capture the overshoot of heat transfer and take more factors showing significant influence on transition into consideration.